The Kinship of Acehnese, Minangkabau and Javanese Language: The Study of Comparative Historical Linguistics - Mukramah Mukramah; Dardanila Dardanila; Tasnim Lubis (Budapest International Research and Critics University, 2022)
This research belongs to the type of linguistic research in the field of comparative historical linguistics with the aim of: see the kinship between the Acehnese language, Minangkabau language and Javanese language. This study uses quantitative methods with lexicostatistical and glotochronological data analysis. Data collection methods used in the form of interviews and listening and recording techniques. After doing research on Acehnese and Minangkabau language, 12 identical word pairs were found, 31 phonemic correspondence word pairs, 8 phonetically similar word pairs, 26 word pairs with 1 different phoneme so that 77 related word pairs were found and from the results of the percentage of kinship, which is 20% and is categorized in the level of language clumps (stock, Acehneseand the Minangkabau language began to split from a proto language between 1,814-1588 BC (counting from 2021). In Acehnese with Javanesefound 17 identical word pairs, 15 phonemic correspondence word pairs, 3 phonetically similar word pairs, 10 word pairs with 1 different phoneme so that 45 pairs of related words were found and from the results the percentage of kinship was 10% and categorized in the Minangkabau language microphylum level.and Javanese began to split from a proto-language between 3,473-3,242 BC (counting from 2021). Furthermore, the Minangkabau language with Javanese26 identical word pairs were found, 36 phonemic correspondence word pairs, 9 phonetically similar word pairs, 21 word pairs with 1 different phoneme so that 92 pairs of related words were found and the percentage of kinship percentage was 30% and categorized in the stock language level. Minangkabau languageand Javanese began to split from a proto-language between 847-693 BC (counting from 2021).